Sport Tourism: A New Educational Concept for Sustainable Development - Trivedi, Dr. Manoj Kumar (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Sports tourism travels from one region, country, state, etc. to another to see sports competitions or competitors. Although sport tourism is not always popular, the number of people who participated in local sport events has increased dramatically over the past ten years. People now travel far to attend their favourite events and are not curious about what promotes popularity. Sport tourism refers to travel experiences in which you can participate or view sport related activities. It is generally accepted that there are three types of sports trips: sporting events, active sports and perfume sports. The type of sports tourists varies from sport to sport. Most generalized statistics show that most sports tourists are men from 18 to 34 years old and belong to the middle class economic group. A better understanding of your studies will help you to get a more accurate statistical ranking of your class, position and age. For example, cricket and rugby fans are usually older and more disposable than regular football and basketball fans. Other sports are consumers of other sports tourists, but all sports have become increasingly popular in recent years. Sport tourism is not difficult to find. Sport tourism is a journey from one place to another that wants to be an audience of all kinds of sporting events. It is the factor that determines whether you are watching a sporting event or travelling with a different schedule. Sports tourism has been on the rise in recent years, but you have to take into account what sports tourists actually are and why they are popular with sports fans. Not only has it steadily increased every year, it has also become one of the biggest reasons for travel and vacation. It seems that more and more people are willing to use their well-earned holiday that their favourite player can actually see. So what is sport tourism? Although the technological advances of recent years have not had a major impact on the sports industry, it is most obvious to see competition so close and personal from a location that is not considered at home. Because you can buy sports tickets online through various access sites, people have access to multiple sources that were not available ten years ago. People are also more aware of where and when the games and competitions take place, so that you can have more time and money to attend the event. Sport tourism has not only found jobs in the technology industry, but has also increased. Keyword: Sports tourism, dramatically, increasingly ,understanding